Portable people counting application using MATLAB - Muhammad Na'im Farhan Mahamud (2023)
Prescriptive analytics is one of the expected sector to be profitable in 2020 with a potential market value of 1.6 billion. Due to that, collecting of data is deem to be important. People counting is one of the main ways to gather data on potential customer for shop owner or useful to maintain security by monitoring the traffic flow of an area. Unfortunately, most of the people counting method uses static camera as an input. This limited the data that could be gather. Using many devices could solve this problem but at the price of increasing cost. To tackle this problem, a portable people counting device is needed. MATLAB is one of the easiest programming method to build a people counting program. By using Viola-Jones algorithm as the base, a face detection program to count people can be build. Raspberry Pi is a mini computer that can be used to run simple program and can be together with its computer module to take picture. Using the image capture by Raspberry Pi, MATLAB will count the number of individual present in the picture. This simple setup will